Nonequilibrium charge-density-wave order beyond the thermal limit - J. Maklar (Nature Portfolio, 2021)
Photo-induced phase transitions triggered by an ultrafast excitation cannot be described within the quasi-equilibrium framework. Here, using time-resolved experimental probes, the authors report a transient charge-density-wave order in TbTe3 and describe it using a model with a non-equilibrium transition temperature.